2017
DOI: 10.1089/ten.tec.2016.0410
|View full text |Cite
|
Sign up to set email alerts
|

Xenogeneic Decellularized Scaffold: A Novel Platform for Ovary Regeneration

Abstract: Women younger than 40 years may face early menopause because of premature ovarian failure (POF). The cause of POF can be idiopathic or iatrogenic, especially the cancer-induced oophorectomy and chemo-or radiation therapy. The current treatments, including hormone replacement therapy (HRT) and cryopreservation techniques, have increased risk of ovarian cancer and may reintroduce malignant cells after autografting. Decellularization technique has been regarded as a novel regenerative medicine strategy for organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 43 publications
8
49
0
1
Order By: Relevance
“…Detergents such as SDS have detrimental effects on the ECM constituents. In addition, trace amount of DNA and cellular antigens can cause serious side effects on the cell viability and functions [ 21 ]. The data from the current study indicated that in short term, the viability of the cells seeded on the decellularized scaffolds was less than those cultured in 2D conventional condition and it may be attributed to the presence of the cell debris and SDS trace within the scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…Detergents such as SDS have detrimental effects on the ECM constituents. In addition, trace amount of DNA and cellular antigens can cause serious side effects on the cell viability and functions [ 21 ]. The data from the current study indicated that in short term, the viability of the cells seeded on the decellularized scaffolds was less than those cultured in 2D conventional condition and it may be attributed to the presence of the cell debris and SDS trace within the scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…For this, it is vital to promote angiogenesis in the hypoxic environment of the artificial ovary. Endothelial cells are crucial in this context, aiding survival of different types of cells by enhancing the quality of revascularization after grafting (Liu et al 2017).…”
Section: Addition Of Isolated Ovarian Stromal Cellsmentioning
confidence: 99%
“…The use of an acellular scaffold is based on the premise that any immune response should be minimal, thereby avoiding the need for immunosuppressant therapy. However, the evaluation process of most published studies only spans a few weeks to a few months (Fishman et al, ; Lange et al, ; Liu et al, ; Maughan et al, ; Mirmalek‐Sani et al, ; Wang, Johnson, et al, ). This raises the concern of monitoring a minimal immune response without considering a potential graft failure occurring later.…”
Section: Translational Limitations Of Biological Scaffoldsmentioning
confidence: 99%
“…However, there are conflicting reports with regard to rejection of xenogeneic and allogeneic acellular scaffolds. Various studies report no or a weak immunogenic response (Cebotari et al, ; Coutu, Mahfouz, Loutochin, Galipeau, & Corcos, ; da Costa et al, ; Elliott et al, ; Fishman et al, ; Jeinsen et al, ; Lange, Shah, Birchall, Sibbons, & Ansari, ; Liu et al, ; Mirmalek‐Sani, Sullivan, Zimmerman, Shupe, & Petersen, ; Sayk, Bos, Schubert, Wedel, & Sievers, ; Wang, Wang, Zhang, Qiang, & Luo, ), whereas others show a significant immune response such as a fibrogenic response, chronic inflammatory reaction, stenosis, noninfectious swelling, edema and lymphatic infiltration, IgG deposition, and activation of complement system (Bastian et al, ; Cicha et al, ; Kasimir et al, ; Maughan et al, ; Rieder et al, ; Ruffer et al, ; Simon et al, ; Spark, Yeluri, Derham, Wong, & Leitch, ; Zheng et al, ). A similar discrepancy in immunogenic response has been noted for some FDA‐approved acellular scaffolds (Simon et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation